New records of phytoplankton for Bangladesh: Division - Cryptophyta (Bangladesh Journal of Plant Taxonomy, 2019)
The paper records 6 species of freshwater phytoplankton from the algal Division Cryptophyta. The species are Cryptomonas pyrenoidifera Geitler, C. caudata Schiller, C. tetrapyrenoidosa Skuja, Chroomonas breviciliata Nygaard, C. reflexa Kiss. and Cyathomonas truncata (Fres.) Fisch HP. These are newly recorded species from Sylhet Division of Bangladesh.